Global economic prospects - June 2016: divergences and risks (Washington, DC, 2016)
"Global growth prospects have deteriorated in 2016. Emerging market and developing economies are facing increased external headwinds, including softer growth in advanced economies. Commodity exporters are struggling with particularly challenging conditions, while commodity importers are thus far showing greater resilience. Global growth is expected to gradually accelerate in 2017-18 but risks to the outlook are increasingly more pronounced. In addition to discussing global and regional economic developments and prospects, this edition of Global Economic Prospects includes two Special Focus essays of critical importance for emerging and developing economies: an analysis of the buildup of private debt in emerging and frontier markets and a quantitative study of uncertainties surrounding global growth. This year marks the 25th anniversary of the Global Economic Prospects. The Global Economic Prospects is a World Bank Group Flagship Report that has, since its inception in 1991, examined international economic developments and prospects, with a special focus on emerging market and developing economies. It has also included analytical essays on a wide range of topical macroeconomic, financial, and structural policy challenges faced by these economies. It is published on a semiannual basis (in January and June). The January edition includes in-depth analyses of topical policy challenges, while the June edition contains shorter analytical essays."